Autologous Platelet-Rich Plasma Eye Drops for the Treatment of Post-LASIK Chronic Ocular Surface Syndrome. (12th December 2017) - Alio, Jorge L.; Rodriguez, Alejandra E.; Abdelghany, Ahmed A.; Oliveira, Renan F.
Abstract : Purpose . To evaluate the efficacy of autologous platelet-rich plasma (E-PRP) eye drops for the treatment of chronic ocular surface syndrome (OSS) following laser in situ keratomileusis (LASIK). Methods . This prospective interventional consecutive clinical study include 156 eyes of 80 patients affected by post-LASIK chronic OSS who were treated with autologous E-PRP 6 times a day as monotherapy for 6 weeks. Results . Dry eye symptoms improved in 85% of the cases. A decrease in at least one quadrant to total disappearance on CFS was observed in 89.6% of the patients who had positive CFS before treatment. Three eyes presented severe punctate keratitis (1.9%) at baseline, all of which healed completely. Conjunctival hyperemia improved in 93.3% of the patients with previous signs of ocular surface inflammation. There was a significant improvement in logMAR CDVA from 0.14 ± 0.19 to 0.06 ± 0.12 (p = 0.000 ), and 74 (71.4%) eyes improved at least 1 line in CDVA. Conclusion . Monotherapy with autologous E-PRP is a well-tolerated, safe, and effective treatment for the management of post-LASIK ocular surface syndrome. Precis . Monotherapy with autologous platelet-rich plasma eye drops has been shown to be an adequate option for the treatment of post-LASIK chronic ocular surface syndrome. This trial is registered with NCT03322917 .